The Effect of Ability and Agility and Their Implications on Competitiveness of Grade XI Vocational High School Students - Maylawati, Windi; Nuryanto, Uli Wildan; Handayani, Yolla Sukma (Jurnal Lingua Idea, 2025)
This study aims to determine how much influence capability and agility have on competitiveness mediated by competitive advantage in students of State Vocational High School (SMK) 4 Cilegon. This study uses a descriptive causality design with quantitative methodology. The sample used is adjusted to the analysis method using the Structural Equation Model (SEM) of 190 respondents. Data collection techniques are primary data and secondary data. Data collection techniques are primary data and secondary data. Primary data is obtained through survey methods, secondary data is obtained through documentation. The analysis techniques used are descriptive statistics, inferential statistical analysis, validity and reliability tests, evaluation of reflective measurement models (outer models), evaluation of structural models (inner models), and evaluation of the goodness and suitability of the model. The results of this study indicate that the coefficient value of the Capability path to Competitiveness through Competitive Advantage is 0.144 positive value, with at statistics of 3.299> 1.96 and a P Value of 0.001 <0.05, so that it proves that Competitive Advantage is able to mediate the influence of Capability on Competitiveness. The coefficient value of the Agility path to Competitiveness through Competitive Advantage is 0.190 positive value, with at statistics of 3.801> 1.96 and a P Value of 0.000 <0.05 so that it proves that Competitive Advantage is able to mediate the influence of Agility on Competitiveness. So, to increase competitiveness can be done through competitive advantage through agility.